Mindful Leadership in Practice Tradition Leads to the Future - Schulte, Volker; Steinebach, Christoph; Veth, Klaske (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book shows why mindful leadership is the key element for supportive management and leadership in the 21st century. It highlights the fundamentals of mindful leadership in philosophy and history in different cultural traditions and shows latest research on mindfulness and digitalization, technology, social networking, and leading-self concepts. The book bridges the past and the future. By combining a range of research perspectives, it connects mindfulness to serving leadership concepts and describes resilience for both individuals and organizations. In addition, it presents theoretical aspects and practical recommendations on how to implement mindful leadership and supportive environments in organizational cultures. The book encompasses history, present leadership challenges and future management perspectives and enables the implementation of models of good practice into daily working life. It includes contributions from researchers of different continents, and offers an international overview of state-of-the art leadership research. This book is of interest to professionals and researchers working on leadership, from the perspective of positive psychology, organizational studies, and wellbeing studies. .
Part 1: Fundamentals of Mindful Leadership - Philosophy, History and Application -- Chapter 1: Analysis of Work and Organization Today -- Chapter 2: A History of the Mindful Leadership Concept -- Chapter 3: Indian Perspectives on Mindful leadership -- Chapter 4: The ideal Emperor from Chinese Perspective -- Chapter 5: The Concept of Mindful Leadership and its Christian Roots -- Chapter 6: Cardinal Virtues and Leadership -- Part II: Traditions and Perspectives of Mindful Leadership -- Chapter 7: Ethics in the Mindfulness Context -- Chapter 8: Taming the Minds - Health and Resilience -- Chapter 9: Digitalization as a Challenge for Mindful Leadership -- Part III: Transfer from Theory to Practice -- Chapter 10: Interventions of Mindfulness and Compassion -- Chapter 11: Mindfulness and Technology -- Chapter 12: Mindfulness in Social Networks - Self-management and Distanced Sociability -- Chapter 13: Mental Training Through Mindfulness.
Keywords: Positive psychology; Psychology, Industrial; Leadership; Personnel management; Well-being.; Positive Psychology; Leadership Psychology; Human Resource Management; Organizational Psychology; Well-Being.